Analysis of social housing laws in Vietnam and other countries and recommendations for Vietnam - Vang-Phu, Tran; Son, Duong Anh (Interacción y Perspectiva, 2025)
The development of social housing constitutes both an economic remedy and a significant political and social obligation of the nation. Through meticulous collaboration between governmental bodies and investors, Vietnam can assimilate the experiences of other nations and adapt them to align with its domestic context. This is regarded as a long-term strategy that fosters social equity. Facilitating social housing for low-income individuals will enhance labor productivity, fostering conditions for sustainable economic growth. This article primarily compares and analyzes the legislation regarding preferential regimes, subjects, and conditions for accessing social housing incentives in Vietnam and several other countries globally. It subsequently proposes methods for Vietnam to enhance its social housing policies.